Ambient Air Pollution, Noise, and Late-Life Cognitive Decline and Dementia Risk - Paul, Kimberly C. (Annu Rev Public Health, 2019)
Exposure to ambient air pollution and noise is ubiquitous globally. A strong body of evidence links air pollution, and recently noise, to cardiovascular conditions that eventually may also affect cognition in the elderly. Data that support a broader influence of these exposures on cognitive function during aging is just starting to emerge. This review summarizes current findings and discusses methodological challenges and opportunities for research. Although current evidence is still limited, especially for chronic noise exposure, high exposure has been associated with faster cognitive decline either mediated through cerebrovascular events or resulting in Alzheimer’s disease. Ambient environmental exposures are chronic and affect large populations. While they may yield relatively modest-sized risks, they nevertheless result in large numbers of cases. Reducing environmental pollution is clearly feasible, though lowering levels requires collective action and long-term policies such as standard setting, often at the national level as well as at the local level.